1996
DOI: 10.2172/434443
|View full text |Cite
|
Sign up to set email alerts
|

Depleted uranium risk assessment for Jefferson Proving Ground using data from environmental monitoring and site characterization. Final report

Abstract: ILos Alarnos National Laboratory, an affimwtbe adionlequal opportunity employer, is opeiated by the University of California forthe U.S. Department of Energy under contfact W-7405ENG36. By acceptance of this article, the pWsht3.r recognnes that the US. Government retains a nonexclusive, royalty-free license to puMish or reproduce the publiihed form of ttuS contribution, or to allow others to do so, for U.S. Government purposes. Los Alamos National Laboratory requests that the Publisher identify this article as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A steady-state model was used to estimate DU uptake by deer and humans, and a computer code designed for risk assessment, RESRAD, was used to estimate the human health risk. For each of the proving groundq, the model indicated that the uptake of uranium by deer is at concentrations that do not pose a health risk to theanimals either radiologically or toxicologically (Ebinger and Hanson 1996a, 1996b, Ebinger et al 1996. The model also indicated that the dose and risk to humans from consumption of deer that live on the proving grounds were insignificant (Ebinger and Hanson 1996a, 1996b, Ebinger et al 1996.…”
Section: Radionuclide Uptake By Ungulatesmentioning
confidence: 99%
See 3 more Smart Citations
“…A steady-state model was used to estimate DU uptake by deer and humans, and a computer code designed for risk assessment, RESRAD, was used to estimate the human health risk. For each of the proving groundq, the model indicated that the uptake of uranium by deer is at concentrations that do not pose a health risk to theanimals either radiologically or toxicologically (Ebinger and Hanson 1996a, 1996b, Ebinger et al 1996. The model also indicated that the dose and risk to humans from consumption of deer that live on the proving grounds were insignificant (Ebinger and Hanson 1996a, 1996b, Ebinger et al 1996.…”
Section: Radionuclide Uptake By Ungulatesmentioning
confidence: 99%
“…It is a well-established Fortran code that has been used and accepted by several government agencies, including the DOE and the Department of Defense. The model is setup in a user-friendly way that is not hard to implement, and it has been used in studies similar to this one by LANL personnel (13bingerand Hanson 1994, 1996a, 1996b, Ebinger et al 1996. The input parameters for RESRAD were largely available from studies that have been done at Area G as part of the Laboratory's environmental monitoring.…”
Section: Model Selectionmentioning
confidence: 99%
See 2 more Smart Citations